HUBUNGAN ANTARA MOTIVASI KERJA DENGAN KINERJA PERAWAT DI WILAYAH KERJA PUSKESMAS TEGAL AMPEL KABUPATEN BONDOWOSO - Irwin Santoni; Said Mardjanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Nurses are human resources who participate in coloring health services in hospitals, because in addition to the dominant number, it is also a profession that provides constant and continuous service for 24 hours to patients every day. The purpose of this study was to determine the relationship between work motivation and nurse performance at the Tegal Ampel Health Center in Bondowoso Regency. This type of research used in this study is correlation analytic research using a cross-sectional approach. The population in this study was 42 respondents. Samples taken were 38 respondents. The results of this study were analyzed using the Spearman Rank. The results of this study are two variables obtained p value of 0.00 (p <a 0.01) which indicates that Ho is rejected, which means there is a significant relationship between Work Motivation and Nurse Performance in the Work Area Tegal Ampel Health Center, Bondowoso Regency. From this research it is expected that the leader can further increase the motivation of nurses in working by giving rewards and it is hoped that nurses can maintain performance in carrying out their duties.